Output stream analysis in a queueing model with working vacation mechanism as a power reduction strategy - Martyna Kobielnik; Wojciech M. Kempa (PLoS ONE, 2026)
The aim of this paper is to analyze the departure process of a queueing model with general independent input stream, exponentially distributed service time, finite buffer and working vacation mechanism. The explicit solution for a Laplace transform of generating function of this characteristic is determined. Utilizing numerical Laplace transform inversion, the time-dependent mean number of jobs served in a time interval is computed. The numerical examples show the behavior of the output stream in dependence on the model parameters, such as interarrival distribution, mean working vacation period duration, the workload in normal and in working vacation mode.